Meritokrasi Adaptif Digital: Pendekatan Baru dalam Reformasi Birokrasi Era Digital - Wulandary, Roro Merry Chornelia; Fithriana, Noora (Universitas Tribhuwana Tunggadewi, 2025)
Bureaucratic reform in Indonesia aims to create professional, efficient, effective, transparent, and accountable governance. However, its implementation faces challenges such as low digital literacy among senior employees and bureaucratic–political interference that hinders the application of meritocracy. This study aims to analyze bureaucratic leadership strategies in implementing adaptive meritocracy in response to digitalization dynamics and bureaucratic–political relations, using a case study of Lowokwaru District, Malang City. The research employed a descriptive qualitative approach with snowball sampling, involving six informants from bureaucratic, academic, and legislative sectors. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings show that meritocracy is relatively well understood at the leadership level but uneven at the operational level. Efforts through online recruitment and digital-based performance evaluation have been made but remain influenced by non-merit practices, seniority, and weak rule enforcement. This study proposes the “Digital Adaptive Meritocracy (DAM)” model, combining competence-based meritocracy, accelerated digital literacy, integrity- driven leadership, peer-learning, and strengthened oversight and rule of law to reinforce bureaucratic reform and accelerate government digitalization. Reformasi birokrasi di Indonesia bertujuan menciptakan tata kelola pemerintahan yang profesional, efisien, efektif, transparan, dan akuntabel. Namun, pelaksanaannya menghadapi tantangan seperti rendahnya literasi digital pegawai senior dan intervensi birokrasi-politik yang menghambat penerapan meritokrasi. Penelitian ini bertujuan menganalisis strategi pimpinan birokrasi dalam menerapkan meritokrasi adaptif terhadap dinamika digitalisasi dan hubungan birokrasi-politik, dengan studi kasus di Kecamatan Lowokwaru, Kota Malang. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik snowball sampling, melibatkan enam informan dari unsur birokrasi, akademisi, dan legislatif. Data dikumpulkan melalui wawancara mendalam, observasi, dan telaah dokumen, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan pemahaman meritokrasi di tingkat pimpinan cukup baik, tetapi belum merata di level pelaksana. Upaya telah dilakukan melalui rekrutmen daring dan penilaian kinerja digital, namun masih dipengaruhi praktik non-merit, senioritas, dan lemahnya penegakan aturan. Penelitian ini merekomendasikan model “Meritokrasi Adaptif Digital (MAD)” yang menggabungkan merit berbasis kompetensi, akselerasi literasi digital, kepemimpinan berintegritas, peer-learning, serta penguatan pengawasan dan supremasi hukum untuk memperkuat reformasi birokrasi dan mempercepat digitalisasi pemerintahan.